Effect of magnetite nanoparticles on the viscoelastic properties of magnetorheological elastomers - Priyandoko, Gigih; Suwandono, Purbo (Jurnal Polimesin, 2025)
Advanced materials known as Magnetorheological Elastomers (MREs) can be used to dampen vibrations. These materials reduce vibration disturbances by responding to an externally applied magnetic field, which alternate their mechanical characteristics. The objective of this research is to explore the effect of incorporating magnetic nanomaterials (Fe₃O₄) on the properties of MRE. The modified material is expected to exhibit enhanced sensitivity to magnetic fields, thereby improving its vibration-damping performance. The MRE mixture utilized in this investigation consists of Carbonyl Iron Powder (CIP), silicone oil, and silicone rubber, with mass percentages of 30%, 5%, and 65%, respectively. The MRE was then given magnetite nanomaterials in amounts of 0.5%, 1%, 1.5%, and 2% of the total weight. To produce MRE, thoroughly mix the silicone rubber with silicone oil and then gradually add the carbonyl iron powder, ensuring uniform dispersion. Once the homogeneity was achieved, the magnetite nanomaterial were incorporated into the MRE mixture with precision. The resulting composite were then cured, optionally under a magnetic field to induce anisotropic alignment. Laboratory tests were conducted on the new material. These tests involved analyzing their elemental composition and evaluating their viscoelastic properties. The research findings indicate the successful development of MREs containing Fe₃O₄ nanomaterials for the purpose of vibration dampening within the frequency range of 1–100 Hz. At a center frequency of 1,167 Hz, MRE-2 (MRE with a 0.5% addition of Fe₃O₄) demonstrated the strongest damping performance, exhibiting the highest tan δ value. This makes MRE-2 the primary choice. MRE-1 is an excellent alternative due to its high stiffness and effective damping at low frequencies.